2009
DOI: 10.1088/0004-637x/694/2/1517
|View full text |Cite
|
Sign up to set email alerts
|

TWO BRIGHT SUBMILLIMETER GALAXIES IN Az= 4.05 PROTOCLUSTER IN GOODS-NORTH, AND ACCURATE RADIO-INFRARED PHOTOMETRIC REDSHIFTS

Abstract: We present the serendipitous discovery of molecular gas CO emission lines with the IRAM Plateau de Bure interferometer coincident with two luminous submillimeter galaxies (SMGs) in the Great Observatories Origins Deep Survey North field (GOODS-N). The identification of the millimeter emission lines as CO at z = 4.05 is based on the optical and near-IR photometric redshifts, radio-infrared photometric redshifts and Keck+DEIMOS optical spectroscopy. These two galaxies include the brightest submillimeter source … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
495
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(542 citation statements)
references
References 122 publications
41
495
4
Order By: Relevance
“…GN20 (Pope et al, 2005), whose redshift was serendipitously discovered by Daddi et al (2009), is a bright SMG in a proto-cluster of multiple DSFGs. GN20 is the brightest SMG in the GOODS-N field with a 850 µm flux density of 20.3 mJy, suggesting a SFR at the level of 1800 M yr −1 (Fig.…”
Section: Gn20mentioning
confidence: 95%
See 2 more Smart Citations
“…GN20 (Pope et al, 2005), whose redshift was serendipitously discovered by Daddi et al (2009), is a bright SMG in a proto-cluster of multiple DSFGs. GN20 is the brightest SMG in the GOODS-N field with a 850 µm flux density of 20.3 mJy, suggesting a SFR at the level of 1800 M yr −1 (Fig.…”
Section: Gn20mentioning
confidence: 95%
“…Sources with z > ∼ 2 are primarily identified via Lyα emission and sources at z < ∼ 1.3 are identified via OII, OIII or Hα. An updated version of the Chapman et al redshift distribution is shown as a dashed-blue line, including DEIMOS-observed radio SMGs from Banerji et al (2011) specifically targeted to fill the redshift desert gap of LRIS, and a handful of high-z 850µm-selected SMGs Daddi et al, 2009;Walter et al, 2012). Also over-plotted is the Lewis et al (2005) and Chapman et al (2003b) phenomenological model 850µm SMG redshift distribution without radio flux selection (dark green dot dashed line).…”
Section: Redshift Distributions Of 850µm-14 Mm-selected Dsfg Populatmentioning
confidence: 99%
See 1 more Smart Citation
“…This so-called star-forming main sequence (MS) is thought to reflect a large duty cycle of star formation in galaxies and exist over a large range of redshifts from z = 0 up to z = 7 (Brinchmann et al 2004;Daddi et al 2007Daddi et al , 2009Elbaz et al 2007;Noeske et al 2007;González et al 2011). Starburst galaxies are considered to be "off-sequence."…”
Section: Introductionmentioning
confidence: 99%
“…Its redshift of z=5.183 enforces the presence of a high redshift tail (z>4) of sub-millimeter bright star-forming (non-AGN/quasar) galaxies (currently there are only about half a dozen systems known) [22][23][24][25][26] . Only a small fraction of sub-millimeter bright sources is expected to be at very high redshift 27 ---it is thus ironic that the first blank-field source belongs to this subgroup.…”
mentioning
confidence: 99%